The development of an integrated corpus for Malay language - Awang Abu Bakar, Normi Sham (Springer Singapore, 2020)
Generally, a corpus serves as the source of data for various types of research. As such, there are a number of Malay corpora being developed to support the needs of the researchers. However, the various corpora of Malay text are distributed and not integrated, where some words are not included or missing in some corpora. The focus of this paper is to develop an integrated corpus that will combine four most comprehensive Malay corpora. The intention is to provide comprehensive coverage of Malay corpora which would be beneficial for any relevant work.